Stability and change in voluntary and paid work in sports associations over two decades - Elmose-Østerlund, Karsten (Politica, 2024)
Four surveys of sports associations form the basis for analyses of 1) the development in voluntary and paid work in the associations over two decades, and 2) the relationship between key characteristics of the associations and voluntary and paid work. Overall, the development in voluntary and paid work in the associations has remained stable in the period. The most significant change is an aging of coaches and leaders over time. Large associations perform better than small ones when it comes to voluntary work and are more likely to hire paid employees. Conversely, old associations and associations in small local areas are less successful when it comes to voluntary work.